Pengaruh Implementasi Sistem Informasi Akuntansi Terhadap Kinerja Manajemen Perusahaan Transportasi yang Terdaftar di Bursa Efek Indonesia Periode 2017-2023 - Bisma Putra Atallah; Agrianti Komalasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to investigate the influence of Accounting Information Sistem (AIS) adoption on managerial performance within transportation companies listed on the Indonesia Stock Exchange (IDX) over the period 2017–2023. The adoption of AIS is assessed using three key financial indicators: net income after taxes, working capital, and total assets. Managerial performance is measured through Return on Equity (ROE), which reflects the company’s efficiency in generating profit from shareholders’ equity.